The reporter and the law : Techniques of Covering the Courts - Denniston, Lyle W (New York Columbia University Press, 1992)
"The Reporter and the Law is an insider's view of how the legal system and the press work together. It explains the framework of the legal process, describes various methods a legal reporter may use to develop sources, describes various methods a legal reporter may use within the system of jurisprudence."
Keywords: Luật học